HUBUNGAN KUALITAS PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN DI PUSKESMAS TATAPAAN MINAHASA SELATAN - Giroth, Maya; Mamuaja, Pricillia; Toar, Jilly (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Service quality and satisfaction in health centers are important and interconnected issues. Health centers as institutions that provide health services need to have human resources that are able to provide quality services to the community, because patient satisfaction depends on service quality. Analyze the relationship between health service quality and patient satisfaction at the Tatapaan Health Center. The type of research used is quantitative research using univariate and bivariate analysis with the determination of the relationship using the Chi Square test. The population in this research amounted to 1288 with a sample of 93 respondents, data collection techniques using a questionnaire. Based on the results of the study it can be concluded that there is a relationship between physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy) with patient satisfaction at Puskesmas Tatapan.